Tourist Classification Based on Consumer Behavior Using XGBoost Algorithm - zalukhu, Jenius; Hasudungan Lubis, Andre (Universitas Medan Area, 2025)
This study discusses the application of the XGBosst Algorithm to Tourists based on consumer behavior. The purpose of this study is to predict or analyze tourist review data, and to help provide and understand needs so as to improve the quality of services offered. Indonesia has great tourism potential thanks to its natural beauty and cultural diversity. This sector plays an important role in the national economy by creating jobs and encouraging the creative industry and hospitality. The presence of tourists increases regional income through taxes and spending in sectors such as hotels, restaurants, and souvenir shops, as well as creating new jobs. In addition to tourists being able to increase income, there is a need for an understanding of each tourist behavior that is important for the development of adaptive and sustainable tourism.